2000
DOI: 10.1056/nejm200002103420602
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin and Factor V Mutations in Women with a History of Thrombosis during Pregnancy and the Puerperium

Abstract: The G20210A prothrombin-gene mutation and factor V Leiden individually are associated with an increased risk of venous thromboembolism during pregnancy and the puerperium, and the risk among women with both mutations is disproportionately higher than that among women with only one mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
246
3
21

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 467 publications
(278 citation statements)
references
References 21 publications
4
246
3
21
Order By: Relevance
“…Other groups have also emphasised the importance of a hereditary AT defi ciency as a high risk thrombophilic disorder, especially during pregnancy [20,21]. In contrast, the presence of a homozygous methylene tetrahydrofolate reductase (MTHFR) C677T mutation did not contribute to the risk of VTE in pregnant women [19,22]. Although not well studied, women with known antiphospholipid syndrome (APS) and previous VTE seem to be at high risk for recurrent VTE during pregnancy.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Other groups have also emphasised the importance of a hereditary AT defi ciency as a high risk thrombophilic disorder, especially during pregnancy [20,21]. In contrast, the presence of a homozygous methylene tetrahydrofolate reductase (MTHFR) C677T mutation did not contribute to the risk of VTE in pregnant women [19,22]. Although not well studied, women with known antiphospholipid syndrome (APS) and previous VTE seem to be at high risk for recurrent VTE during pregnancy.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Hypoxemic growth-restricted fetuses also demonstrate a whole range of abnormalities that persist in adult life [4][5][6][7][8][9][10] . Cross-sectional studies in pregnancies with growth-restricted fetuses have shown that increased impedance to flow in the uterine and umbilical arteries is associated with fetal hypoxemia and acidemia 11,12 , resulting in:…”
Section: Hypoxemic Hypoxia (Uteroplacental Insufficiency)mentioning
confidence: 99%
“…Hypoxemic growth-restricted fetuses also demonstrate a whole range of abnormalities that persist in adult life [4][5][6][7][8][9][10] . Cross-sectional studies in pregnancies with growth-restricted fetuses have shown that increased impedance to flow in the uterine and umbilical arteries is associated with fetal hypoxemia and acidemia 11,12 , resulting in:(1) Failure of the normal development of maternal placental arteries into low-resistance vessels and therefore reduced oxygen and nutrient supply to the intervillous space 13 ; (2) Reduction in the number of placental terminal capillaries and small muscular arteries in the tertiary stem villi and therefore impaired maternal-fetal transfer 14 .Doppler ultrasound has enabled the non-invasive confirmation of the so-called 'brain-sparing' effect in human fetuses 15 . …”
mentioning
confidence: 99%
“…thrombophilia is substantially increased. The risk of VTE in pregnant women may be further amplified by the type of underlying genetic predisposition, like, homozygosity for a mutation, the presence of multiple mutations (multigenic defects) or thrombophilic anomalies [16][17][18][19].Thrombophilia and adverse pregnancy outcome Preeclampsia, abruptio placenta, intrauterine growth restriction (IUGR) and intrauterine fetal death (IUFD) greatly contribute to maternal and fetal morbidity and mortality. Their causes are unknown, but all of them may be associated with abnormal placental vasculature and disturbances of hemostasis leading to inadequate maternal-fetal circulation [11][12][13][14][15]20,21].…”
mentioning
confidence: 99%